2013
DOI: 10.1002/jgrg.20096
|View full text |Cite
|
Sign up to set email alerts
|

In search of greener pastures: Using satellite images to predict the effects of environmental change on zebra migration

Abstract: [1] Historically, ungulate migrations occurred in most grassland and boreal woodland ecosystems, but many have been lost due to increasing habitat loss and fragmentation. With the rate of environmental change increasing, identifying and prioritizing migration routes for conservation has taken on a new urgency. Understanding the cues that drive long-distance animal movements is critical to predicting the fate of migrations under different environmental change scenarios and how large migratory herbivores will re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 75 publications
4
72
0
1
Order By: Relevance
“…), zebras ( Equus burchelli ) responding to precipitation (Bartlam‐Brooks et al . ) and snow cover depth in moose ( Alces alces ) (Singh et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…), zebras ( Equus burchelli ) responding to precipitation (Bartlam‐Brooks et al . ) and snow cover depth in moose ( Alces alces ) (Singh et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…208 With approximately 50-70% of the Earth's land surface currently modified for human 209 activities (1), patterns of biodiversity and ecosystem functions worldwide are changing (2). The 210 expanding footprint of human activities is not only causing the loss of habitat and biodiversity, 211 but also affects how animals move through fragmented and disturbed habitats.…”
Section: Global Loss Of Vagility Alters a Key Ecological Trait Of Animentioning
confidence: 99%
“…For instance, a powerful predictive migration model for the migratory zebra, Equus burchelli antiquorum, was developed using NDVI data to evaluate how their timing and pace of movement is affected by spatio-temporal changes in the environment (Bartlam-Brooks et al, 2013). Another example also showed that elephants tracked an intermediate value of NDVI in the Marsabit protected area in Kenya, corresponding to the "surfing the green wave" hypothesis (Bohrer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%